Primary Epithelioid Angiosarcoma of the Thyroid in a Patient Occupationally Exposed to Radiations - Marina, Michela; Corcione, Luigi; Serra, Maria Francesca; Ferri, Teore; Silini, Enrico Maria; Ceresini, Graziano (Frontiers in Endocrinology, 2018)
Background: Angiosarcoma (AS) of the thyroid is a rare and aggressive tumor. Its incidence is higher in iodine-deficient areas but cases unrelated to endemic goiter have been reported. Case Presentation: We describe a case of a 63-year-old Italian man living in a non-iodine-deficient area, with no previous diagnosis of thyroid disease with a history of radiation exposure. The patient—an interventional cardiologist who had worked for 15 years in an angiographic room- came to the clinical observation because of the rapid onset of dyspnea and dysphonia. Computed tomography (CT) showed a 13-cm inhomogeneous neck mass, originating from the left thyroid lobe which caused displacement and stenosis of the trachea. The patient underwent diagnostic fine-needle aspiration that was followed by total thyroidectomy and lymphadenectomy of central and left lateral cervical nodes. The final pathological diagnosis was epithelioid angiosarcoma (EAS), high grade. The preoperative staging by CT of the head, neck, abdomen, chest and pelvis was negative. At pathological staging, the tumor was angionvasive but it was limited to the thyroid; no lymphnode metastases were detected. Chemotherapy with Epirubicin and Ifosfamide was administered for 4 cycles and, then, it was discontinued due to significant bone marrow toxicity. Conclusion: One year after diagnosis, the CT of neck, abdomen, chest, and pelvis were negative. At 2 years after diagnosis, the FDG-PET was negative with no evidence of the disease at CT Due to the known association between the occurrence of angiosarcoma after radiation therapy it is tempting to speculate that in this patient the presence of thyroid EAS may be linked to radiation exposure.The patient is still alive at 62 months after diagnosis. He is on a follow-up program by a 6-month /1-year neck, chest, abdomen, and pelvis CT evaluation with no signs of metastases.